Surface engineering of gadolinium oxide nanoseeds with nitrogen-doped carbon quantum dots: an efficient nanocomposite for precise detection of antibiotic drug clioquinol. (8th February 2022) - Devi, Ramadhass Keerthika; Ganesan, Muthusankar; Chen, Tse-Wei; Chen, Shen-Ming; Liu, Xiaoheng; Ali, M. Ajmal; Almutairi, Saeedah M.; Sethupathi, Murugan
Abstract : Nitrogen-doped carbon quantum dot decorated gadolinium oxide nanoseeds as an electrode modifier for the sensitive electrochemical detection of the antibiotic drug clioquinol in urine samples. Abstract : Here we present the hydrothermal synthesis of nitrogen-doped carbon quantum dot (N-CQD) decorated gadolinium oxide (N-CQD@Gd2 O3 ) nanocomposite for the first time. The nanocomposite features a nanoseed-like structure rather than the typical Gd2 O3 nanorod-like structure. The presence of N-CQDs plays a dynamic role in the specific structural formation of the nanocomposite, which has been evaluated through physiochemical characterizations. Also, for the first time, the nanocomposite was employed as an electrode material for the sensitive electrochemical detection of an antibiotic drug, clioquinol (CQL), using an amperometric technique. Based on the oxidation peak current response of CQL, the influence of experimental factors such as the nanocomposite loading concentration/volume, scan rate, sample concentration, and accumulation time were investigated. As a consequence, the developed N-CQD@Gd2 O3 /GCE sensor exhibits a low detection limit of 2.1 nM and a high sensitivity of 3.6 μA μM −1 cm −2 for the detection of CQL. Furthermore, the developed sensor has a high level of stability, repeatability, and reproducibility. Furthermore it performed well in real sample analysis with good recovery results, suggesting its practical applicability.